2016
DOI: 10.1007/s11356-016-7300-2
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of PAHs from agricultural soils treated with oil shale combustion ash: an experimental study

Abstract: The present study focuses on the fate of polycyclic aromatic hydrocarbons (PAHs) in soils amended with oil shale ash (OSA). Leachability studies to assess the release of PAHs to the environment are essential before the application of OSA in agriculture. A quantitative estimation of the leaching of PAHs from two types of soil and two types of OSA was undertaken in this study. Two leaching approaches were chosen: (1) a traditional one step leaching scheme and (2) a leaching scheme with pretreatment, i.e.., incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The US Environmental Protection Agency (EPA) has highlighted 16 unsubstituted PAHs as priority pollutants that need monitoring. Numerous investigations found that PAHs are widely distributed in the environmental media such as sediments, 10 agriculture soil, 11 urban soil, 12 roadside soil, 13,14 industry-affected soil, 15,16 dump sites, 17 and mine-impacted soil. [18][19][20] Soil pollution in the coal mine area is mainly ascribed to coal exploitation, processing, and utilization.…”
Section: Introductionmentioning
confidence: 99%
“…The US Environmental Protection Agency (EPA) has highlighted 16 unsubstituted PAHs as priority pollutants that need monitoring. Numerous investigations found that PAHs are widely distributed in the environmental media such as sediments, 10 agriculture soil, 11 urban soil, 12 roadside soil, 13,14 industry-affected soil, 15,16 dump sites, 17 and mine-impacted soil. [18][19][20] Soil pollution in the coal mine area is mainly ascribed to coal exploitation, processing, and utilization.…”
Section: Introductionmentioning
confidence: 99%